Predictors of entrepreneurial intentions: The role of prior business experience, opportunity recognition, and entrepreneurial education - Tian, Hongyun; Akhtar, Shamim; Qureshi, Naveed Akhtar; Iqbal, Shuja (Frontiers in Psychology, 2022)
Entrepreneurship and its influence on the development of the economy are significant in competitive global advancement. Entrepreneurs need entrepreneurial intentions to improve the commercial environment of the country. Therefore, studying entrepreneurial intentions’ influencing predictors is vital for business development. We collected data from SMEs’ employees of the developing country and used partial least square structured equation modeling to analyze the proposed relationships. The results assist the literature extension and practically contribute to developing entrepreneurs’ intentions through education and opportunity recognition. The findings aid the institutions in improving course planning along with the establishment of practical business setups. This study facilitates the government's ideas of commencing entrepreneurial businesses through proper resource provisions to the entrepreneurs.